(untitled) (Ottawa, Canada, 1998)
This book enables novices and professionals alike to jointly assess the extent to which the benefits of development are shared- and by whom. It presents leading-edge analysis on theory and practice of participatory evaluation around the world. The most comprehensive volume available on the subject, it is a valuable tool for practitioners and policymakers in all areas of development.
Keywords: Evaluation research (Social action programs),Rural development; Evaluation